American and European Muslim Female Bloggers Increase Their Preaching Efforts in Social Media - Kurmanaliyev, Maxat (Religions, 2024)
This article investigates the evolving landscape of religious agitation in the digital age, focusing specifically on the religious propaganda activities of female bloggers in the USA and Europe. In today’s society, religious discourse is increasingly being held on various social media channels, shaping a new trend in religious agitation. Muslim female bloggers are emerging as influential voices on these platforms, employing diverse preaching methods and discussing certain feminine topics aimed at Muslim women. This research employs a mix of quantitative, qualitative, and empirical methodologies to discover the peculiarities of the sermons delivered by them. An extensive analysis was performed to evaluate their rising influence, audience interaction, and how they differ from their male counterparts. Additionally, this study examines how Muslim female bloggers are transforming the face of the Islamic call in the USA and Europe by adopting a feminist approach. Importantly, our research work highlights the activities of non-hijabi Muslim bloggers who are influencing Western Muslim women in social media. We examine the religious discourse of Western female and male Muslim bloggers by juxtaposing their preaching activities. Besides, a comparison is made between the female Muslim bloggers in Western regions and the Islamic world. This article underscores the profound influence of social media on religious discourse and highlights their contributions to religious discourse in the digital age.